A nonlinear fibre beam-column model for partially encased composite columns incorporating local buckling effect. (1st June 2023) - Song, Yuchen; Li, Jie; Yam, Michael C.H.; Chen, Yiyi
Abstract: Partially encased composite (PEC) columns are being widely used as vertical load carrying members in high-rise building structures. The complex structural behaviour of PEC columns at ultimate and failure states, related to local buckling of steel section and confinement effect of concrete, has posed significant difficulties and computational costs for accurate analysis of these members. To address this issue, this paper presents a nonlinear fibre beam-column (FBC) model for efficient and accurate analysis of PEC columns. A 2D Euler-Bernoulli beam element based on geometrically exact beam theory is employed, which has fibre cross sections accounting for the material nonlinearity of steel and concrete. A generalised effective width method (GEWM) is developed and integrated in the FBC model to simulate the stress redistribution in the steel section due to the progression of local and post-local buckling. Numerical examples demonstrate that the proposed FBC model can reasonably predict the behaviour of short PEC columns under concentric and eccentric compression, as well as the global buckling behaviour of long PEC columns. The computational cost of the proposed FBC model is considerably lower than that of 3D finite element analysis. The numerical examples also show that the incorporation of the local buckling effect (GEWM) leads to decreases in the ultimate and post-peak loads predicted by the FBC model. The effect of local buckling becomes insignificant for long PEC columns with length-to-depth ratios greater than 15. Highlights: A nonlinear fibre beam-column (FBC) model is developed for partially encased composite (PEC) columns. 2D Euler-Bernoulli beam element based on geometrically exact beam theory is adopted. Material nonlinearity of steel and concrete are considered in fibre sections. Local and post-local buckling in PEC columns is simulated by a generalised effective width method. Numerical examples are provided to demonstrate the accuracy of the proposed model.